Increasing venoarterial extracorporeal membrane oxygenation flow puts higher demands on left ventricular work in a porcine model of chronic heart failure - Hála, Pavel; Mlček, Mikuláš; Ošťádal, Petr; Popková, Michaela; Janák, David; Bouček, Tomáš; Lacko, Stanislav; Kudlička, Jaroslav; Neužil, Petr; Kittnar, Otomar (Journal of translational medicine, 2020)
BACKGROUND: Venoarterial extracorporeal membrane oxygenation (VA ECMO) is widely used in the treatment of circulatory failure, but repeatedly, its negative effects on the left ventricle (LV) have been observed. The purpose of this study is to assess the influence of increasing extracorporeal blood flow (EBF) on LV performance during VA ECMO therapy of decompensated chronic heart failure. METHODS: A porcine model of low-output chronic heart failure was developed by long-term fast cardiac pacing. Subsequently, under total anesthesia and artificial ventilation, VA ECMO was introduced to a total of five swine with profound signs of chronic cardiac decompensation. LV performance and organ specific parameters were recorded at different levels of EBF using a pulmonary artery catheter, a pressure-volume loop catheter positioned in the LV, and arterial flow probes on systemic arteries. RESULTS: Tachycardia-induced cardiomyopathy led to decompensated chronic heart failure with mean cardiac output of 2.9 ± 0.4 L/min, severe LV dilation, and systemic hypoperfusion. By increasing the EBF from minimal flow to 5 L/min, we observed a gradual increase of LV peak pressure from 49 ± 15 to 73 ± 11 mmHg (P = 0.001) and an improvement in organ perfusion. On the other hand, cardiac performance parameters revealed higher demands put on LV function: LV end-diastolic pressure increased from 7 ± 2 to 15 ± 3 mmHg, end-diastolic volume increased from 189 ± 26 to 218 ± 30 mL, end-systolic volume increased from 139 ± 17 to 167 ± 15 mL (all P < 0.001), and stroke work increased from 1434 ± 941 to 1892 ± 1036 mmHg*mL (P < 0.05). LV ejection fraction and isovolumetric contractility index did not change significantly. CONCLUSIONS: In decompensated chronic heart failure, excessive VA ECMO flow increases demands and has negative effects on the workload of LV. To protect the myocardium from harm, VA ECMO flow should be adjusted with respect to not only systemic perfusion, but also to LV parameters.
Keywords: Heart Failure; Heart failure; Animals; Hemodynamics; Artificial cardiac pacing; hemodynamika; funkce levé komory srdeční; Extracorporeal Membrane Oxygenation; Extracorporeal membrane oxygenation; mimotělní membránová oxygenace; srdeční selhání; Heart ventricles; zvířata; Myocardium; myokard; prasata; Swine; Ventricular Function, Left